FBM@Solidarity Palestine - UiTM, Faculty of Business and Management (UiTM, 2023)
On November 29, 2033, the Business Economics Students Society Selangor (BESSS), in collaboration with Students Affairs at the Faculty of Business Management, UiTM Puncak Alam, orchestrated an impactful initiative titled "FBM@SOLIDARITY PALESTINE". The event transformed the FBM Fest at the Faculty of Pharmacy Parking Lot into a purposefilled gathering space. Distinguished participants included the esteemed Dean of the Faculty of Business Management, Professor Dr. Firdaus Abdullah, alongside VIPs, UiTM lecturers, and staff members. Ustaz Mohd Norhisyam Azman, Dr. Rabiatul Munirah Apandi, and a passionate student representative from BESSS delivered insightful talks.